Regulation of Proline Metabolism Under Salt Stress in the Psychrophilic Diatom Fragilariopsis Cylindrus (Bacillariophyceae) - Krell, Andreas; Plettner, Ina; John, Uwe; Dieckmann, Gerhard; Funck, Dietmar (Journal of Phycology, 2007)
Fragilariopsis cylindrus (Grunow) Willi Krieger, a bipolar psychrophilic and highly abundant diatom, experiences strong shifts in salinity during the formation of sea ice. We investigated the effects of osmotic stress due to an increased salt concentration from 34 to 70 practical salinity units (PSU) in conjunction with a temperature decrease from 0˚C to -4˚C on the anabolic and catabolic pathways of proline metabolism. Gene expression levels of Δ1-pyrroline-5-carboxylate synthase (P5CS) strongly decreased by a factor of 17.3 in the 70 PSU ⁄ 0˚C treatment, whereas copy numbers of ornithine d-aminotransferase (δ-OAT) increased 7.6-fold. Transcript levels of D1-pyrroline-5-carboxylate reductase (P5CR) and proline dehydrogenase (ProDH) were also slightly up-regulated by 2.5 and 2.88, respectively. This contrasts with findings in higher plants where a reverse regulation of P5CS and δ-OAT was observed and indicates that under elevated external salinities, the ornithine route is preferred to the glutamate pathway in F. cylindrus. Photosynthetic quantum yield at PSII instantly dropped from 0.61 to 0.24 after the upshift in salinity, which confirmed a detrimental effect of elevated salt concentrations on the photosynthetic machinery. Reduced photosynthetic energy capture might explain the preference for the ornithine route over the more energyconsuming proline route. Salt proved to be the dominating stressor, while an additional temperature decrease appeared to have an ameliorating effect. published